Carbon nanotube-mediated wireless cell permeabilization: drug and gene uptake. (December 2011) - Raffa, Vittoria; Gherardini, Lisa; Vittorio, Orazio; Bardi, Giuseppe; Ziaei, Afshin; Pizzorusso, Tommaso; Riggio, Cristina; Nitodas, Stephanos; Karachalios, Theodoros; Al-Jamal, Khuloud T; Kostarelos, Kostas; Costa, Mario; et al.
Aim: This work aims to exploit the 'antenna'' properties of multiwalled carbon nanotubes (MWCNTs). They can be used to induce cell permeabilization in order to transfer drugs (normally impermeable to cell membranes) both in in vitro and in vivo models.Material & Methods: The performance of the MWCNTs as receiver antenna was modeled by finite element modeling. Once the appropriate field has been identified, the antenna properties of MWCNTs were investigated in sequential experiments involving immortalized fibroblast cell line (drug model: doxorubicin chemothererapeutic agent) and living mice (drug model: bcl-2 antiapoptotic gene) following stereotactic injection in the cerebral motor cortex.Results: Finite element modeling analysis predicts that our MWCNTs irradiated in the radiofrequency field resemble thin-wire dipole antennas. In vitro experiments confirmed that combination of MWCNTs and electromagnetic field treatment dramatically favors intracellular drug uptake and, most importantly, drug nuclear localization. Finally, the brain of each irradiated animal exhibits a significantly higher number of transfected cells compared with the appropriate controls.Conclusion: This wireless application has the potential for MWCNT-based intracellular drug delivery and electro-stimulation therapies.